2015
DOI: 10.17533/udea.rccp.v28n3a3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microencapsulated organic acids and essential oils on growth performance and intestinal flora in weanling pigs

Abstract: Efecto de los ácidos orgánicos y aceites esenciales microencapsulados sobre el crecimiento y flora intestinal en cerdos destetos Efeito dos ácidos orgânicos e óleos essenciais microencapsulados sob a flora intestinal e o crescimento em suínos desmamados SummaryBackground: dietary supplementation with organic acids and essential oils has positive effects on growth improvement and nutrient digestion. Microencapsulation of nutrients allow for the slow release of core materials in a specific period and/or environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…In our previous reports, the dietary supplementation of a microencapsulated organic acid blend with inorganic acids such as MCFAs or essential oil had positive effects on the growth performance and nutrient digestibility in growing (13) and finishing pigs (14,15), but not yet in layer hens. Thus, the objective of the present study was to evaluate the effects of a microencapsulated organic acid blend with MCFAs on egg production, weight, quality, fecal microflora, and nutrient digestibility in laying hens.…”
Section: Introductionmentioning
confidence: 87%
“…In our previous reports, the dietary supplementation of a microencapsulated organic acid blend with inorganic acids such as MCFAs or essential oil had positive effects on the growth performance and nutrient digestibility in growing (13) and finishing pigs (14,15), but not yet in layer hens. Thus, the objective of the present study was to evaluate the effects of a microencapsulated organic acid blend with MCFAs on egg production, weight, quality, fecal microflora, and nutrient digestibility in laying hens.…”
Section: Introductionmentioning
confidence: 87%
“…In our previous reports, the dietary supplementation of MOE had shown positive effects on the performances in poultry (Mohammadi Gheisar et al 2015) and finishing pigs (Cho et al 2014). The study on the effect of MOE supplementation in sows is limited.…”
Section: Introductionmentioning
confidence: 96%
“…Organic acids (OA) and essential oils (EO) supplementation has shown a functional similarity to antibiotics, thus offering an interesting alternative to growth-promoting source in livestock nutrition. Previous reports indicated that OA and EO supplements in pig diets had beneficial effects on growth performance (Cho et al 2006;Wang et al 2009;Grilli et al 2010;Gong et al 2014), nutrient digestibility (Yan et al 2010;Cho et al 2014) and both of them are appropriate antibiotic alternatives in swine diets (Rota et al 2004;Mroz 2005). Similar benefits generated by the inclusion of OA and EO to sows diets have been reported by other authors (Kis & Bilkei 2003;Allan & Bilkei 2005;Miller et al 2009;Kluge et al 2010;Ariza-Nieto et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other studies have suggested that essential oils improved growth performance, measured in terms of BW, ADG, ADFI, and G : F, because they stimulated intestinal enzymes, leading to increased nutrient digestibility, balance of microbiota, and feed intake (Huang et al, 2010;Li et al, 2012b;Lan et al, 2016). Additionally, a previous study revealed that a microencapsulated feed containing organic acids and essential oil added to finishing pig diet could increase growth performance, nutrient digestibility of DM, and energy (Cho et al, 2014). More recently, lactic acid bacteria were proved to be effective in this regard.…”
Section: Discussionmentioning
confidence: 98%